Pharmacology : - Katzung, Bertram G. (Appleton & Lange, 1993)
Short discussion of the major concepts that underlie basic principles or specific drug groups. Explanatory figures and tables. Review questions followed by answers and explanations. Drug trees in drug-oriented chapters that visually organize drug groups. A list of high-yield terms and definitions you need to know. Skill Keeper Questions that prompt you to review previous material to understand links between related topics. A checklist of tasks you should be able to perform upon completion of a chapter. Summary tables that list the important drugs and include key information about their mechanisms of action, effects, clinical uses, pharmacokinetics, drug interactions, and toxicities.